Design of a morphing airfoil - Yap, Chor Yen (2012)
Recent advancements in smart materials enable energy efficient solid state actuation of morphing airfoil. The Macro Fiber Composite (MFC) is one of the most popular piezoelectric actuator for this application in recent developments.